2017
DOI: 10.1080/14756366.2017.1306521
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NS2B-NS3 protease and furin inhibition on West Nile and Dengue virus replication

Abstract: West Nile virus (WNV) and Dengue virus (DENV) replication depends on the viral NS2B-NS3 protease and the host enzyme furin, which emerged as potential drug targets. Modification of our previously described WNV protease inhibitors by basic phenylalanine analogs provided compounds with reduced potency against the WNV and DENV protease. In a second series, their decarboxylated P1-trans-(4-guanidino)cyclohexylamide was replaced by an arginyl-amide moiety. Compound 4-(guanidinomethyl)-phenylacetyl-Lys-Lys-Arg-NH in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
39
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 39 publications
3
39
0
Order By: Relevance
“…The hemagglutinin precursor HA0 is cleaved by furin into HA1 and HA2. Results obtained with this screening assay usually correlate well with the antiviral activity of inhibitors in cell‐based infection studies as shown previously for H7N1 and H5N1 HPAIV, canine distemper virus, Semliki Forest virus, chikungunya virus, West Nile virus, and Dengue‐2 virus . In the current study, strong differences in potency were found in this assay, as shown by the Western blot in Figure .…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…The hemagglutinin precursor HA0 is cleaved by furin into HA1 and HA2. Results obtained with this screening assay usually correlate well with the antiviral activity of inhibitors in cell‐based infection studies as shown previously for H7N1 and H5N1 HPAIV, canine distemper virus, Semliki Forest virus, chikungunya virus, West Nile virus, and Dengue‐2 virus . In the current study, strong differences in potency were found in this assay, as shown by the Western blot in Figure .…”
Section: Resultssupporting
confidence: 87%
“…A slight concentration‐dependent inhibition was observed for the aminopyridine analogue 20 , which provided ≈10‐fold reduced DENV‐2 titers at 50 μ m , whereas a negligible inhibition was found for compounds 14 , 17 , 19 , and 23 (data not shown). Therefore, only the most potent inhibitors 24 and 27 were selected for a further dose‐response assay, using the recently investigated compound 4 and the nucleotide analogue ribavirin as reference inhibitors (Figure ) . Also in this assay, the strongest antiviral efficacy was found for the reference compound 4 , which is more potent than ribavirin at similar concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previously described linear inhibitors revealed as ignificant activity against numerousf urin-dependent pathogenic viruses in cell culture experiments at lower micromolar concentrations. [20,24,29,[36][37][38][39] Due to limited tolerability of the most potent compounds in mice, [29] we prepared different types of new macrocyclic analogues to find alternative inhibitor structures and determined their potencya gainst furin. The development of these compounds began with the crystal structure of the hexapeptided erivative 1 in complex with furin.…”
Section: Discussionmentioning
confidence: 99%